Open arterial reconstruction of multiple hepatic artery aneurysms in a patient with hereditary hemorrhagic telangiectasia: A case report. Issue 46 (November 2016) - Ozawa, Hirotsugu; Ohki, Takao; Kanaoka, Yuji; Maeda, Koji; Hagiwara, Shin
Abstract: Background: Hereditary hemorrhagic telangiectasia (HHT) is characterized by mucocutaneous telangiectasia and visceral vascular malformations (VMs). Liver involvement with VMs may lead to high-output cardiac failure, portal hypertension, and biliary disease. There is no curative treatment for the disease, and liver transplantation is indicated for life-threatening complications. Herein, we report a case of multiple hepatic artery aneurysms (HAAs) in a patient with HHT in which open arterial reconstruction was performed. There have only been a few case reports on HAA occurring with HHT. Thus, this case provides important information for the management of HHT-associated HAAs. Case summary: A 62-year-old female with known HHT was referred to our facility to seek further treatment for a giant HAA. She denied any symptoms except recurrent epistaxis. A computed tomography (CT) scan revealed a right HAA with a diameter of 72 mm, in addition to 2 other minor HAAs. The CT scan also revealed the VMs that were scattered in the liver, and a continuously dilated and tortuous artery existing from the celiac trunk to the right and left hepatic arteries. We performed open arterial reconstruction of the HAAs. Her postoperative course was uneventful. Conclusions: When treating HAAs, there are a variety of options. However, hepatic VMs might affect HHT patients in various ways postprocedurally. Ligation and embolization of the hepatic artery may lead to complications, such as massive hepatic necrosis. Hepatectomy should be avoided if possible, because a postoperative hyperperfusive state in the remaining liver can cause adverse events. We believe that arterial reconstruction of HHT-associated HAAs might reduce the risk of postprocedural complications with minimal hemodynamic changes in the liver, thus obviating the need for hepatectomy or liver transplantation.